Disaster on the Titanic - Messner, Kate (New York : Scholastic Inc., 2019)
This time the mysterious box transports the golden retriever Ranger back to the shipyards of Belfast in 1912, where a ship is being prepared for her maiden voyage, and when he saves young Patrick Murphy from being crushed by falling boards, Ranger expects to be transported home; when he is not, he knows that somehow his job is not finished--but then, Ranger has never heard of the Titanic, and knows nothing of the fate that awaits Patrick, and all the other people on board.
Includes bibliographical references.
4.1
3-6
640L
Keywords: Titanic (Steamship) -- Juvenile fiction; Golden retriever -- Juvenile fiction; Time travel -- Juvenile fiction; Shipwrecks -- North Atlantic Ocean -- Juvenile fiction; Survival -- Juvenile fiction; North Atlantic Ocean -- Juvenile fiction; Adventure stories; Titanic (Steamship) -- Fiction; Golden retriever -- Fiction; Dogs -- Fiction; Time travel -- Fiction; Shipwrecks -- Fiction; Survival -- Fiction; North Atlantic Ocean -- Fiction; Adventure and adventurers -- Fiction; Time-travel fiction; Action and adventure fiction